Altered expression of type II sodium/phosphate contransporter in polycystic kidney disease - Vogel, Moritz; Kränzlin, Bettina; Biber, Jörg; Murer, Heini; Gretz, Norbert; Bachmann, Sebastian (Journal of the American Society of Nephrology, 2000)
Abstract. Renal phosphate (Pi) absorption is mediated via the type II sodium/Pi cotransporter (NaPi-2) in the brush border membrane (BBM) of proximal tubules. Simultaneous detection of NaPi-2 mRNA by in situ hybridization and of NaPi-2 immunoreactivity by immunohistochemistry was performed to investigate the distribution of the cotransporter in healthy control rats and during progression of autosomal dominant polycystic kidney disease (ADPKD). The purpose of the study was to disclose a relation between proximal tubular cell differentiation and NaPi-2 expression. In controls, NaPi-2 expression was present in the entire proximal tubule. In the Han:SPRD (cy/+) model for ADPKD, the proximal nephron is primarily affected by the cystic changes. Epithelial proliferation and impaired epithelial-matrix interaction result in a loss of cell differentiation that eventually leads to cystic enlargement of the nephron. Normal expression of NaPi-2 in this model was found only in tubules with intact BBM. Loss of BBM and cellular interdigitation were paralleled by the loss of NaPi-2 in situ hybridization and immunoreactive signals. These changes were moderate and focal in 2-mo-old rats and generalized all over the cortex after 8 mo. Advanced renal damage in the older PKD group was associated with mild phosphaturia, which suggests functional insufficiency of tubular NaPi-2 reabsorption. These data show how proliferative changes and loss of tubular epithelial differentiation in ADPKD may prevent functional expression of the NaPi-2 system in the proximal tubule in a rapidly progressive manner. NaPi-2 in proximal tubule BBM is suggested to play an important role in impaired tubular absorption of Pi in renal disease.